Why Mary Astell's Theory of Virtue is Not Inconsistent - Rickless, Samuel C. (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2025)
There is an apparent inconsistency at the heart of Mary Astell’s theory of virtue, for she seems committed to contradictory propositions: (1) that virtue involves alignment of all passions with their proper objects; and (2) that virtue involves the elimination or extirpation of at least some passions, such as pride, anger, hatred, and overwhelming sorrow. Jacqueline Broad (2015) has tried to solve this interpretive problem by suggesting that Astell recommends a two-step process for the virtuous management of one’s passions, with (1) occurring first and in the short term and (2) occurring second and in the long term. This essay agrees with Broad that Astell does not fall into inconsistency, but for different reasons. It argues that Astell consistently treats self-esteem, anger, hatred, and sorrow as unmoralized (i.e., neither virtuous nor vicious) passions that cannot, and hence should not, be extirpated, but that vicious forms of these passions, such as in the case of pride and overwhelming sorrow but also in the case of excessive anger and hatred, should be removed from the soul through proper redirection and adjustment in both the short term and the long term.